PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN MAKRAME SISWA KELAS V SD NEGERI 145 PEKANBARU - Kurniawan, David Hendra; Antosa, Zariul; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Base of problem in this research is the value of the students still under KKM. It is unknown, because the teacher does not involve students in the learning process, the teacher does not use the media during the learning process to take place, many students who are less interested in the teaching-learning process because it is considered less interesting, and presence of dependent students to other students who are superior,It is necessary for the improvement of learning with immediate application of learning models. Direct instructional model is a learning process that is more centered on the teacher (teacher centered), the teacher becomes the main information source and giver. Although the direct instruction method is used in addition to lectures and equipped or supported with the use of the media, the emphasis remains on the admissions process knowledge (subject matter) rather than on the search process and the construction of knowledge, and tend to emphasize the delivery of information sourced from textbooks, reference or personal experience. The study is in the form of classroom action research (PTK). This study aims to improve the skills makrame Elementary School fifth grade students 145 Pekanbaru. After the adoption of direct learning model can be applied, the data obtained from quantitative data. With the formulation of the problem is "Does the application of the model pembelajara can directly improve the skills makrame fifth grade students of SDN 145 Pekanbaru?". The quantitative data in the form of tests students' knowledge and skills through repetition test cycle. Activity teachers each meeting there is an increase. At the first meeting of teachers activity percentage is 65%. The second meeting of teacher activity increased by 15% to 80%. The third meeting increased 5% to 85%. At the fourth meeting increased 5% to 90%. The average percentage of the activity of teachers in the first cycle was 72.5%. While the average percentage of the activity of the teacher on the second cycle increased by 15% to 90%. in the first cycle, the daily tests of skills I, which completed 24 students with an average (70.58%), and incomplete 7 students with an average (29.42%). Experienced an increase from a base score of 26.47%. In the daily tests are completed the second cycle 31 students with an average (91.17%), and incomplete 3 students with an average (8.83%) and an increase from the previous cycle of 20.59%, while the increase from the base score to the second cycle of 29.41%.Keywords: Application of Direct Learning Model. Skills.Macrame.